(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The study was conducted in Iloilo City in order to determine the organoleptic and phytochemical results of the herbal tea from three different species of plants. The experiment involved three factors such as plant species, levels of maturity and amount of ground leaves. This was a 3 * 3 * 3 factorial experiment in CRD. The study consisted of organoleptic and phytochemical evaluation. The data gathered were subjected to both descriptive and inferential statistics with the results of the latter interpreted at the alpha level of 0.05. The study revealed the the sensory evaluation revealed that the factor such as plant species and amount of ground leaves significantly affected the aroma of herbal tea. Significantly best tea was obtained from malunggay at 4 g and 6 g. The rest of the factors and the interactions did not significantly affect the aroma of herbal tea. However, generally the four sensory attributes were verbally described as excellent and were not significantly affected by maturity of the leaves. The factor such as plant species also significantly affected the color, flavor and general acceptability of herbal tea. The rest of the factors and the interactions did not significantly affect the color, flavor and general acceptability of herbal tea. The different formulations of tea powder were generally positive in phytochemicals. Malunggay herbal tea had significantly the best color, flavor and general acceptability among the plant species. The panelists rated the color, flavor, aroma and general acceptability of the three plant species, three levels of maturity and three amounts all as excellent. The phytochemical analysis of the three plant species differed in terms of reducing sugars where guava and malunggay was positive while guyabano was negative. The rest of the phytochemicals were mostly present in the three species. Alkaloids and flavonoids were present in considerable amounts in the three plant species namely guava, guyabano and malunggay. Glycosides, sponins, coumarin and betacyanin were present in the three plant species. Anthraquinones were present in guava and malunggay and considerable amounts were found in guyabano. Reducing sugars were present in guava and malunggay but not in guyabano. Terpenoids and emodins were found in considerable amounts in guava and malunggay but present in lesser amounts in guyabano. The sensory attributes differed significantly in the three plant species in terms of color, flavor and general acceptability. The aroma significantly differed by plant species and amounts of ground leaves per sachet.